Differential Effects of Dietary MSG on Hippocampal Dependent Memory Are Mediated by Diet - Holton, Kathleen F.; Hargrave, Sara L.; Davidson, Terry L. (Frontiers in Neuroscience, 2019)
Introduction. Free glutamate is a common dietary flavor enhancer and is also an important excitatory neurotransmitter in the body. A good number of food additives which contain glutamate are found in the Western Diet, and this diet has also been linked to obesity, a condition which increases risk of cognitive dysfunction. Objective. To examine the effects of dietary glutamate on hippocampal and non-hippocampal memory function, and whether consuming a diet high in fat/sugar could influence any observed associations. Methods. Sixty-four adult male Sprague-Dawley rats were trained concurrently on two different discrimination problems: (1) Pavlovian serial feature negative (sFN) discrimination, in which a brief tone stimulus was reinforced with sucrose pellets when it was presented alone (T+ trials) and nonreinforced on trials when it was preceded by the presentation of a brief light (LT- trials); and (2) a simple discrimination (SD) problem in which a white noise (WN+) cue was reinforced with sucrose pellets and a clicker (C-) stimulus was not reinforced. Previous research has shown that sFN, but not SD performance, depends on the functional integrity of the hippocampus. After solving both problems, the rats were assigned to one of four ad libitum-fed diet groups, matched on weight and discrimination performance: 1) standard low-fat chow, 2) chow + monosodium glutamate (MSG), 3) high fat, high sugar western-style diet (WD), or 4) WD + MSG. Results. After 14 weeks, rats fed WD had higher adiposity than rats fed chow. Consistent with previous findings, rats fed WD exhibited impaired performance on the sFN problem, but not on the SD, relative to rats fed chow. Adding MSG to WD abolished this impairment, whereas rats fed chow + MSG had impaired sFN performance compared to rats fed chow alone. No differences in performance on the SD task were observed. Conclusion. MSG has differing effects on memory mediated by the hippocampus, depending on underlying diet, with negative effects occurring in low adiposity animals on a typical chow diet, but beneficial effects occurring in higher adiposity animals on a Western-type diet. More research will be needed to further explore the cause of these differential effects.